2016
DOI: 10.3390/en9040301
|View full text |Cite
|
Sign up to set email alerts
|

Code-to-Code Validation and Application of a Dynamic Simulation Tool for the Building Energy Performance Analysis

Abstract: Abstract:In this paper details about the results of a code-to-code validation procedure of an in-house developed building simulation model, called DETECt, are reported. The tool was developed for research purposes in order to carry out dynamic building energy performance and parametric analyses by taking into account new building envelope integrated technologies, novel construction materials and innovative energy saving strategies. The reliability and accuracy of DETECt was appropriately tested by means of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In order to help readers to understand the sources of errors, as well as eventual bugs to be detected and fixed, arising during the development of a BEPS tool, the author detailed the refinement iterative process carried out for minimizing the differences between the DETECt simulation results and the reference ones, suitably provided within the reliability test suite. All the results were in good agreement with those provided by the BESTEST [34].…”
Section: Contents Of the Special Issuesupporting
confidence: 87%
See 1 more Smart Citation
“…In order to help readers to understand the sources of errors, as well as eventual bugs to be detected and fixed, arising during the development of a BEPS tool, the author detailed the refinement iterative process carried out for minimizing the differences between the DETECt simulation results and the reference ones, suitably provided within the reliability test suite. All the results were in good agreement with those provided by the BESTEST [34].…”
Section: Contents Of the Special Issuesupporting
confidence: 87%
“…In this framework, the development and the adoption of building energy performance simulation (BEPS) tools is crucial and highly recommended for promoting the building integration of renewable energy technologies, toward the design of the next generation of buildings (e.g., NZEBs). The development and validation procedure relative to a BEPS tool, also adopted for performing innovative building-plant simulation, based on renewable technologies, is reported by Buonomano [34]. The author describes the steps of the development and validation procedure of a BEPS tool, named DETECt.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…where f is the external surface view factor, T sky is the sky temperature, ε is the emissivity of the surface, α is the average spectral absorption factor (calculated through spectral reflectance curves integrated across the whole solar range), G bm accounts for the long-wave radiation exchange on the internal surface of the considered thermal zone, I is the total solar radiation flux (depending on geometrical relationships implemented in a specific subroutine [107]). Note that further details about the solar radiation subroutine, not reported for the sake of brevity, are available in reference [108]. The calculation of the solar radiation entering through transparent elements and distributed within the internal space is carried out by means of the selected absorption, reflection, and view factors.…”
Section: Heat Flow Calculation Proceduresmentioning
confidence: 99%
“…Further details of the developed mathematical model and concerning the related capabilities are available in references [72,108].…”
Section: Heat Flow Calculation Proceduresmentioning
confidence: 99%
“…In this context, reflective roof or insulation coatings have been utilized for increasing the energy savings potential of building envelopes, and several studies can be found in the literature, such as [18,19,[23][24][25][26][27]. Nevertheless, due to the low cost, concrete or ceramic tiles are widely used in roofs in Brazil.…”
Section: Introductionmentioning
confidence: 99%